Virus-associated pharynx tumors in a 16-year-old boy: the description of the clinical case - Tatiana V. Gorbunova (IP Habib O.N., 2020)
Objectives. The relationship between the development of the number of malignant tumors in children and viruses is well known. The etiological role of the EpsteinBarr virus in the development of undifferentiated nasopharyngeal cancer (NPC) has been well studied. The effect of human papillomavirus (HPV) on the occurrence and development of NPC in children is not sufficiently understood.